Noncompliance to Antihypertensive Medication in Patients with Essential Hypertension attending Dhaka Medical College Hospital - Rashid, Md Mamun ur; Haque, Md Mohaimenul; Islam, Md Shafiqul; Parvin, Most Firoza; Kahhar, Azizul (TAJ: Journal of Teachers Association, 2023)
Introduction: Medication noncompliance is a necessary but neglected factor for the negative cardiovascular outcome. Despite various studies on the issue, the factors behind noncompliance still need to be explored properly. Therefore, this study was conducted to determine the magnitude and factors associated with noncompliance with antihypertensive Medication. Materials and Methods: This is a cross-sectional study that was conducted on 200 hypertensive patients in Dhaka Medical College Hospital for six months. Patients were included by purposive sampling, aged 18-70 years, and the duration of diagnosis of at least three months. In addition, demographic data, hypertension diagnosis, antihypertensive drugs, factors related to noncompliance, knowledge of hypertension, perception, and family support were included in the questionnaire. Result: About 85% of the patients were non-compliant with treatment in their course of illness, and the main reason behind it was forgetfulness (48.2%). Other factors were inability to buy, side effects, busy schedule, intentionally, bored, and traveling. The highest prescribed drug was beta blockers (41%). Eighty percent of the patients knew that uncontrolled hypertension could lead to stroke, and 54% knew it could lead to heart disease. The majority (87.5%) of the participant went for follow-up only when they felt hypertensive. Regarding perception, 63% of patients felt hypertension is not a curable disease. Furthermore, though all patients were asked for follow-up by their physician, 94% missed their follow-up. Conclusion: Despite the availability of various types of effective antihypertensive drugs, many patients experience difficulty controlling hypertension due to noncompliance. Patient and family member education efficiently prevented many factors behind the disobedience. However, further studies with large sample sizes in multiple centers could explain this more precisely. TAJ 2022; 35: No-2: 103-110